Detection of antibiotic resistance coding gene in Klebsiella pneumoniae bacteria isolated from broiler chickens in West Java, Indonesia - Safika Safika, Zumala Nilasari, Fachriyan Hasmi Pasaribu (Journal of Applied Pharmaceutical Science, 2022)
Antibiotic resistance is now a global health issue. Antibiotic abuse leads microorganisms to grow resistant to a variety of antibiotics. Antibiotic resistance and resistant genes in Klebsiella pneumoniae in broiler chickens in West Java Province were investigated. Broilers from Bogor and Sukabumi were used to obtain 200 cloacal swab samples. Cultures on MacConkey agar, Gram staining, biochemistry test, and polymerase chain reaction (PCR) were used to isolate and identify the samples. The Kirby–Bauer disk diffusion method was used to investigate antibiotic sensitivity, and PCR was used to detect resistance genes. A total of 20% of the samples tested positive for K. pneumoniae. Among other drugs, K. pneumoniae isolates demonstrated resistance to erythromycin (100%), oxytetracycline (97.5%), ampicillin (97.5%), tetracyclines (95%), nalidixic acid (95%), enrofloxacin (EN) (87.5%), EN (82.5%), ciprofloxacin (75.0%), gentamicin (45.0%), and chloramphenicol (25%). All isolates (100.0%) had gyrA and blaTEM genes, 85.0% had tetA genes, and 52.5% had ermB genes, according to the molecular test. Klebsiella pneumoniae may be isolated and identified from broiler chickens in West Java, Indonesia, according to this study. Klebsiella pneumoniae isolated possessed gyrA, blaTEM, tetA, and ermB-resistant genes and was multidrug-resistant.
Keywords: Antimicrobial resistance, broiler, chickens, Klebsiella sp, resistant gene